(untitled) (PERcursos Linguísticos, 2023)
This study aims to understand, through the narratives of trainees in the Languages undergraduate program, the necessary linguistic and didactic-pedagogical knowledge for teaching, according to the Base Nacional Comum Curricular (BNCC). We believe that at this stage of teacher training, English teachers-to-be are exposed to a variety of teaching knowledge that will be developed throughout their entire lives. The theoretical framework is based on: (i) the Dialogical Discourse Analysis – DDA (BAKHTIN, 2006), which considers language a communicative event in which responsive and responsible acts are intertwined, (ii) the concept of literacy (STREET, 2014) and Oliveira’s (2014) discussion about the essential knowledge for teachers of additional languages. The methodology of this qualitative research follows an interpretive approach and was developed in two stages: (i) the collection of reading diaries, developed by the students in the Supervised Internship curricular component, in the semester 2023/1, and (ii) data analysis based on the DDA. As results, we found that both the principles of the BNCC and the understanding of language/language are present in the students’ narratives in different ways, which directly influence their practices in the internship.